Pelatihan Aplikasi Google Suite Untuk Meningkatkan Kinerja Organisasi di Majelis Buddhayana Indonesia Provinsi Jawa Timur - Haryanto Tanuwijaya; Tjandrarini (Ekobis Abdimas, 2022)
The Indonesian Buddhist Council (MBI) is an association based on the principles of Pancasila and the 1945 Constitution of the Republic of Indonesia, based on Buddhadharma and taking refuge under the Great Sangha of Indonesia (Sagin). MBI East Java (Jatim) is one of 27 MBI Regional Administrators in Indonesia. As a religious organization, MBI East Java has many activities, both internal and community services. During the Covid-19 pandemic, various organizational activities, especially management coordination, were hampered and there was even a decline in organizational performance due to the PPKM policy from the government. Based on this experience, the management of MBI East Java intends to take advantage of applications that provide various integrated applications in organizational management to improve organizational performance. Based on these problems, training for Google Suite or G-suite applications was held that provides integrated services such as Gmail, Docs, Drive, Calendar, Meet, and other integrated applications. The G-suite application training is carried out using explanation, demonstration and hands-on practice methods during the training. The G-suite application training to improve organizational performance at MBI East Java has been carried out well and smoothly as evidenced by the average questionnaire score of 3.74. This training material was assessed by participants as having conformity with the needs of the organization with the highest score of 3.94. The quality of the training materials is also considered good. The quality of the material in service to quality is considered to state that the training is very beneficial for them as indicated by the 4.0 questionnaire score. The participants rated the training materials useful for them with a score of 3.75, but they needed more practice time in training as indicated by the questionnaire score of 3.38 which was the lowest score in the evaluation of this training. Overall, the implementation of this community service has succeeded in improving the skills of the administrators in using the G-suite application to improve organizational performance.